2019
DOI: 10.1002/ejic.201801218
|View full text |Cite
|
Sign up to set email alerts
|

The Niecke Biradicals and Their Congeners – The Journey from Stable Biradicaloids to Their Utilization for the Design of Nonlinear Optical Properties

Abstract: Biradicals within organic chemistry are known to be of fleeting existence. They can be traced only by femtosecond spectroscopy and/or corresponding trapping experiments. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 133 publications
0
24
0
Order By: Relevance
“…A selection of diradicaloids is given in Figure . Some might look like diradicals at first sight, such as meta -benzyne and the four-membered ring 6π-electron system, , as their Lewis structures each have two unpaired electrons. Some are readily recognized as diradicaloids, even if they have seemingly normal Lewis structures, for instance, para -quinodimethane and oligoacenes.…”
Section: On the Way To Diradicaloidsmentioning
confidence: 99%
“…A selection of diradicaloids is given in Figure . Some might look like diradicals at first sight, such as meta -benzyne and the four-membered ring 6π-electron system, , as their Lewis structures each have two unpaired electrons. Some are readily recognized as diradicaloids, even if they have seemingly normal Lewis structures, for instance, para -quinodimethane and oligoacenes.…”
Section: On the Way To Diradicaloidsmentioning
confidence: 99%
“…Biradicals are known as intermediates in bond formation and bond cleavage processes . Therefore in the past three decades, detailed investigations of their chemistry have attracted increasing interest, especially the synthesis, characterization and reactivity of singlet biradicals derived from cyclobutanediyls by isolobal replacement of carbon atoms by other main group elements , , , . In 1995 Niecke et al synthesized and isolated the first singlet biradical, a C 2 P 2 four‐membered carbon centred biradical .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Therefore in the past three decades, detailed investigations of their chemistry have attracted increasing interest, especially the synthesis, characterization and reactivity of singlet biradicals derived from cyclobutanediyls by isolobal replacement of carbon atoms by other main group elements. [2,4,5,29] In 1995 Niecke et al synthesized and isolated the first singlet biradical, a C 2 P 2 four-membered carbon centred biradical. [30] The Niecke group has extensively studied the reactivity of this biradical with respect to ringopening reactions, isomerization, redox activity and reactions with small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…However, A is intrinsically unstable and highly susceptible to electrocyclization leading to 1,2‐dihydrodiphosphete B , in sharp contrast to the carbon congener, butadiene . Both bicyclo[1.1.0]butane ( C ) and cyclobutane‐1,3‐diyl ( D ) have been explored as the valence isomers of A …”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Both bicyclo[1.1.0]butane (C) and cyclobutane-1,3-diyl (D) have been explored as the valence isomers of A. [14][15][16][17][18][19][20][21][22] The use of appropriate kinetic stabilization substituents such as the supermesityl (Mes*; 2,4,6-tri-t-butylphenyl) group is a promising approach for isolating A by retarding the thermodynamically preferred electrocyclization process. [8][9][10] However, previous studies revealed that the oxidative homocoupling of the silyl-substituted phosphavinyllithium afforded the corresponding 1,2-dihydrodiphosphete (3,4-diphosphacyclobutene) 1 exclusively: the corresponding heavier butadiene species was not observed at all (Figure 2).…”
Section: Introductionmentioning
confidence: 99%